Pengendalian Penyakit Busuk Pangkal Batang Kelapa Sawit secara Kultur Teknis - Hari Priwiratama; Agus Eko Prasetyo; Agus Susanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Effort to manage basal stem rot disease (BSR) caused by Ganoderma boninense could be conducted through several cultural practice approaches. Four series of field experiments was conducted to observe the effectiveness of cultural practice methods for controlling the epidemic of basal stem rot due to G. boninense. Sanitation trial consisted of three treatments i.e root sanitation with big hole planting system, big hole without root sanitation, and standard replanting system as comparison. Hole in hole and standard planting system were compared in the hole in hole trial. Digging and mounding trial was conducted in four treatments, i.e. digging and mounding with teer and Trichoderma, digging and mounding with Trichoderma, mounding with Trichoderma, and infected palm without any treatment as comparison. Meanwhile, a 4 m × 4 m trench was used in the isolation trench trial. Annual observation was conducted to determine the disease incidence of BSR in each trial. Results showed that all methods could prevent palms from G. boninense infection in the early stage of oil palm development. Proper root sanitation delayed G. boninense infection until 2 years after treatment (YAT), hole in hole planting system was able to suppress disease incidence up to 7 YAT, digging and mounding was useful to prolong the life of the infected palms up to 3 YAT, meanwhile the use of isolation trench was demonstrated to prevent G. boninense infection to neighboring palms up to 2 YAT.